2023
DOI: 10.1039/d3fo01093g
|View full text |Cite
|
Sign up to set email alerts
|

Soy protein compared with whey protein ameliorates insulin resistance by regulating lipid metabolism, AMPK/mTOR pathway and gut microbiota in high-fat diet-fed mice

Abstract: The findings of soy protein versus whey protein supplementation on glycemic regulation are inconsistent. The aim of the present study was to investigate the preventive effect of soy protein isolate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…6). MTH is a gene closely related to longevity, and down‐regulation of MTH could reduce the production of free radicals and effectively enhance the antioxidant capacity of fruit flies 59 …”
Section: Discussionmentioning
confidence: 99%
“…6). MTH is a gene closely related to longevity, and down‐regulation of MTH could reduce the production of free radicals and effectively enhance the antioxidant capacity of fruit flies 59 …”
Section: Discussionmentioning
confidence: 99%
“…Du et al [33] reported that daily FBT administration (400 mg/kg) inhibited the hepatic steatosis and adipocyte size increment associated with HFD [23], which aligns with the findings of our current investigation. The levels of hepatic lipid metabolismrelated genes were measured (Figure 3), as the liver is a vital organ involved in lipid homeostasis [35]. In the current study, FLT and FBT administration (400, 800 mg/kg BW) improved lipid metabolism in HFD-induced obese mice by downregulating the levels of fatty acid synthesis-related genes (SREBP-1c, ACC, and FAS) and upregulating the levels of fatty acid oxidation-related genes (PPARα and AMPK).…”
Section: Flt and Fbt Alleviated Lipid Homeostasis And Oxidative Stressmentioning
confidence: 99%